Temporal and spatial influences incur reconfiguration of Arctic heathland soil bacterial community structure. (16th September 2015) - Hill, Richard; Saetnan, Eli R.; Scullion, John; Gwynn‐Jones, Dylan; Ostle, Nick; Edwards, Arwyn
Summary: Microbial responses to Arctic climate change could radically alter the stability of major stores of soil carbon. However, the sensitivity of plot‐scale experiments simulating climate change effects on Arctic heathland soils to potential confounding effects of spatial and temporal changes in soil microbial communities is unknown. Here, the variation in heathland soil bacterial communities at two survey sites in Sweden between spring and summer 2013 and at scales between 0–1 m and, 1–100 m and between sites (> 100 m) were investigated in parallel using 16S rRNA gene T‐RFLP and amplicon sequencing. T‐RFLP did not reveal spatial structuring of communities at scales < 100 m in any site or season. However, temporal changes were striking. Amplicon sequencing corroborated shifts from r‐ to K ‐ selected taxon‐dominated communities, influencing in silico predictions of functional potential. Network analyses reveal temporal keystone taxa, with a spring betaproteobacterial sub‐network centred upon a B urkholderia operational taxonomic unit (OTU) and a reconfiguration to a summer sub‐network centred upon an alphaproteobacterial OTU. Although spatial structuring effects may not confound comparison between plot‐scale treatments, temporal change is a significant influence. Moreover, the prominence of two temporally exclusive keystone taxa suggests that the stability of Arctic heathland soil bacterial communities could be disproportionally influenced by seasonal perturbations affecting individual taxa.